Reform in basic telecommunications and the WTO negotiations: The Asian experience - Patrick Low; Aaditya Mattoo (World Trade Organization (WTO), 1998)
This paper examines liberalization of the basic telecommunications sector in a number of Asian countries and the role of the General Agreement on Trade in Services (GATS) in this process. It begins by explaining the working of the GATS as a mechanism for multilateral liberalization efforts. It then presents a description of the reforms taking place in the telecom regimes of selected Asian countries, and of the commitments these countries made in the recent GATS negotiations. The paper explores the reasons why governments have taken advantage of the GATS negotiations to make multilateral market-opening commitments, even though they were not pursuing export interests. The paper also considers the limits to what was achieved by way of liberalization commitments in the negotiations. Allowing greater foreign equity participation without liberalizing the conditions of entry may raise national welfare concerns. Furthermore, certain governments could have taken greater advantage of the opportunity under GATS to precommit to future liberalization.
Keywords: F13; K33; L43; L51; 330; Telecommunications; GATS; services; trade liberalization; investment